POTENSI DANA DESA TERHADAP PEMBANGUNAN DESA - Shaskya Wida Oktiena; Nungki Khunaini (JURNAL EKOMBIS, 2020)
Village funds are funds sourced from the APBN that are transferred to the APBD which are prioritized on activities related to the implementation of development and empowerment of village communities. Policies in regulating the amount of village funds that enter the region are fully regulated by the government (state). The implementation of village funds has been carried out since 2015. Village funds as funds to realize community welfare and equitable development have the aim of improving village public services, overcoming and alleviating poverty problems, advancing the rural economy sector, overcoming problems of inter-village development gaps, strengthening the subject of development (community village). The use of village funds to finance village development in an effort to improve the welfare of the community is one of the priorities of village funds that need special attention in their implementation. This article is intended to analyze the potential of village funds for village development. This research uses descriptive qualitative type. Data collection method in this research is literature study by searching several articles related to village funds and village development and the contribution of village funds to village development activities. The results showed that village funds have the potential to increase village development in order to achieve the welfare of village communities by considering the role and accountability of the government in managing and using village funds as well as the level of community participation / awareness of village fund management in efforts to realize village development to improve the welfare of village communities .Keywords : Village Development, Village Fund.